GENDER DISCRIMINATIONS AS REFLECTED IN THE FILM ON THE BASIS OF SEX - Ayu Rengganis, Dewi; Fadhelah Aulia Hamidah, Galuh; Kartiningsih, Rindrah; Utungga Pasopati, Rommel (TANDA, 2023)
This journal intends to evaluate Ruth Bader Ginsburg, the major female character in the film On The Basis of Sex (2018), who encounters gender prejudice in her daily life. The story is based on the true story of Ruth Bader Ginsburg, who experienced prejudice and stereotype in America about 1950s. This article would like to explore reflections of gender discriminations in the film On The Basis Of Sex. To study the subject, gender discrimination theory by Cassie Damewood is used by employing qualitative method. On The Basis Of Sex discusses societal beliefs and gender stereotypes that still exist today. Ruth Ginsburg is a successful woman who successfully overcame traditional gender norms and achieved gender equality, which significantly altered her life and society. She struggles to fulfill her dream of becoming a lawyer. She experienced injustice because of her gender. Ruth reflects liberal feminism when she champions equality on education, work, and justice. The conclusion of this study is any gender discrimination should never stop women to fight for equality and to find any uniqueness for them to move forward.